Genetic origin and composition of a natural hybrid poplar Populus × jrtyschensis from two distantly related species. Issue 1 (December 2016) - Jiang, Dechun; Feng, Jianju; Dong, Miao; Wu, Guili; Mao, Kangshan; Liu, Jianquan
Abstract Background The factors that contribute to and maintain hybrid zones between distinct species are highly variable, depending on hybrid origins, frequencies and fitness. In this study, we aimed to examine genetic origins, compositions and possible maintenance ofPopulus × jrtyschensis, an assumed natural hybrid between two distantly related species. This hybrid poplar occurs mainly on the floodplains along the river valleys between the overlapping distributions of the two putative parents. Results We collected 566 individuals from 45 typical populations ofP. ×jrtyschensis, P. nigra andP. laurifolia . We genotyped them based on the sequence variations of one maternally inherited chloroplast DNA (cpDNA) fragment and genetic polymorphisms at 20 SSR loci. We further sequenced eight nuclear genes for 168 individuals from 31 populations. Two groups of cpDNA haplotypes characteristic ofP. nigra andP. laurifolia respectively were both recovered forP. ×jrtyschensis . Genetic structures and coalescent tests of two sets of nuclear population genetic data suggested thatP. ×jrtyschensis originated from hybridizations between the two assumed parental species. All examined populations ofP. ×jrtyschensis comprise mainly F1 hybrids from interspecific hybridizations betweenP. nigra andP. laurifolia. In the habitats ofP. × jrtyschensis, there are lower concentrations of soil nitrogen than in the habitats occupied by the other two species. Conclusions Our extensive examination of the genetic composition ofP. × jrtyschensis suggested that it is typical of F1 -dominated hybrid zones. This finding plus the low concentration of soil nitrogen in the floodplain soils support the F1 -dominated bounded hybrid superiority hypothesis of hybrid zone maintenance for this particular hybrid poplar.